Self-medication practices and perceived associated health implications: a review - Hamza, Baneen Abbas; Fadheel, Qayssar Joudah (Pharmakeftiki, 2025)
Self-medication – defined as the use of pharmaceutical products without a formal prescription from a licensed healthcare provider – is a globally prevalent practice, particularly in developing countries where medications are more readily accessible and healthcare costs remain prohibitive. This behaviour includes the consumption of over-the-counter (OTC) drugs, the reuse of previously prescribed medications, and the sharing of pharmaceuticals among family members. Although self-medication offers certain advantages, such as economic feasibility, ease of access, and perceived autonomy, it simultaneously poses significant health risks. These include misdiagnosis, potential drug-drug interactions (DDIs), and the development of antimicrobial resistance (AMR), especially in the context of inappropriate antibiotic use. The prevalence of self-medication is notably high in South Asian countries, driven by factors such as prior personal health experiences and pervasive pharmaceutical marketing strategies. Commonly used medications in this context include analgesics and antibiotics, often employed in order to treat minor ailments such as upper respiratory tract infections and cephalalgia. Despite its utility in managing non-serious health conditions, improper self-medication – particularly involving antibiotics – can lead to severe consequences, including AMR and adverse drug reactions. DDIs may further exacerbate these risks, potentially resulting in critical outcomes such as renal impairment. In order to mitigate these threats, it is imperative to strengthen patient education, advocate for the judicious use of OTC medications, and enhance public awareness regarding the risks associated with unsupervised pharmaceutical consumption.